COMPARATIVE STUDY ON THE ASSESSMENT OF VO2MAX BY ERGOSPIROMETRIE OR FIELD TEST - Trofin Petrut Florin; Honceriu Cezar; Cojocaru Dumitru (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
The maximum oxygen consumption (VO2max) can be considered an important indicator of cardio-respiratory aptitude in endurance effort, being used both in predicting performance in sports and in personal training plans. The research paper carries out a study aimed at evaluating VO2max by ergospirometry compared to its assessment by using a field test. This study used for ergospirometry Cosmed FittMate Pro equipment with direct gas exchange analyzer during a progressive effort protocol on cycle ergometer while the field test used the VAMEVAL testing. New female subjects, aged between 20 and 25 years have conducted both tests at an interval of 72 hours. The recorded outcomes do not indicate statistically significant differences, which proves the validity of the VO2max testing, both in the field testing and ergospirometry.